0333 Gender and Menopausal Status Correlate with Sleep Surgery Outcome. (25th May 2022) - Taheri, Nazlie; Hong, Yeon; Abdelwahab, Mohammad; Huang, Allen; Fleury, Thomaz; Liu, Stanley
Abstract: Introduction: With recognized anatomic and physiological differences between males and females, it is critical to describe outcomes of sleep surgery with respect to gender. The objective of this study is to compare the subjective and objective outcomes of phase I sleep surgery with respect to gender and age. Methods: This was a retrospective review of adult subjects who presented to a single center for surgical evaluation of OSA from January 2019 to June 2021. Only subjects undergoing phase I surgery (turbinate reduction, septoplasty, nasal valve surgery, DOME, tonsillectomy, preservation palatopharyngoplasty, tongue base reduction, genioglossus advancement, and upper airway stimulation), who also had complete pre and post-operative PSG data were included. Objective measures were post operative apnea hypopnea index (AHI), oxygen desaturation index (ODI), and lowest oxygen saturations (LOS). Subjective outcomes include Epworth Sleepiness Scale (ESS), and Nasal Obstruction and Septoplasty Effectiveness (NOSE) questionnaires. The groups were matched for age and pre-operative BMI. Results: Twenty-six subjects met inclusion criteria, of which 12 were female and 13 were males. Of the females 5 were post-menopausal. The average male pre-operative AHI, ODI, lowest SpO2, and ESS were 34.4± 28.7, 30.2±28.3, 80.7±6.6, and 10.3±5.6 respectively. Pre-operative values for females were, 31.9±19.2, 18.47±20.4, 82.8±8.4, and 12.5±4.8 respectively. The average AHI reduction in males was 25.5± 29.1, and for females it was 8.3±21.0 (p=0.042). Specific to post-menopausal females, Average AHI reduction was 8.3± 21.0 and 20.2±16.6 for pre-menopausal females (p=0.01). The average ESS reduction in males was 3.1±3.2 (p=0.22) and for females 5.5±5.4 (p=0.001). Conclusion: In this cohort, pre-menopausal women have higher objective surgical success rate (Sher's criteria) after phase I surgery as compared to post-menopausal women. Men respond more favorably than women to phase I surgery based on AHI reduction, but not with ESS. Gender and menopause status are important factors in evaluating efficacy of sleep surgery. Support (If Any):